Lymphoma in reindeer (Rangifer tarandus tarandus L.) - Järplid, Bertil; Rehbinder, Claes (Rangifer, 1995)
In reindeer, only one case of lymphoma, a multiple cutaneous malignant lymphoma, has been reported hitherto. This communicaton describes two additional cases of lymphoma in reindeer. One was a young adult, of unreported sex, slaughtered 1994 in Harads in northern Sweden and the other an elderly female slaughtered 1974 in Strömstad in middle Sweden.